A new scale to assess health-facility level management: the development and validation of the facility management scale in Ghana, Uganda, and Malawi - Paul Mubiri; Freddie Ssengooba; Thomasena O'Byrne; Adelaine Aryaija-Keremani; Justine Namakula; Kingsley Chikaphupha; Moses Aikins; Tim Martineau; Frédérique Vallières (BMC, 2024)
Abstract Background The increased recognition of governance, leadership, and management as determinants of health system performance has prompted calls for research focusing on the nature, quality, and measurement of this key health system building block. In low- or middle-income contexts (LMIC), where facility-level management and performance remain a challenge, valid tools to measure management have the potential to boost performance and accelerate improvements. We, therefore, sought to develop a Facility-level Management Scale (FMS) and test its reliability in the psychometric properties in three African contexts. Methods The FMS was administered to 881 health workers in; Ghana (n = 287; 32.6%), Malawi (n = 66; 7.5%) and Uganda (n = 528; 59.9%). Half of the sample data was randomly subjected to exploratory factor analysis (EFA) and Monte Carlo Parallel Component Analysis to explore the FMS' latent structure. The construct validity of this structure was then tested on the remaining half of the sample using confirmatory factor analysis (CFA). The FMS' convergent and divergent validity, as well as internal consistency, were also tested. Results Findings from the EFA and Monte Carlo PCA suggested the retention of three factors (labelled 'Supportive Management', 'Resource Management' and 'Time management'). The 3-factor solution explained 51% of the variance in perceived facility management. These results were supported by the results of the CFA (N = 381; χ2 = 256.8, df = 61, p < 0.001; CFI = 0.94; TLI = 0.92; RMSEA [95% CI] = 0.065 [0.057-0.074]; SRMR = 0.047). Conclusion The FMS is an open-access, short, easy-to-administer scale that can be used to assess how health workers perceive facility-level management in LMICs. When used as a regular monitoring tool, the FMS can identify key strengths or challenges pertaining to time, resources, and supportive management functions at the health facility level.